Role of Endobronchial Ultrasound Guided Transbronchial Needle Aspiration in the Diagnosis of Intraocular Inflammation in India – Our Experience. (18th August 2019) - Sudheer, Bhagya; Agarwal, Manisha; Sharma, Deepa; Mehta, Ravi; Babu, Kalpana
ABSTRACT: Purpose : To report our experience of using Endobronchial ultrasound-guided transbronchial lymph node aspiration (EBUS-TBNA) in assessing the etiology in uveitis from two tertiary eye-care centers in India. Materials & Methods : Retrospective interventional case series. Results : A total of 99 patients of uveitis who underwent EBUS-TBNA were included in the study. Mycobacterium tuberculosis (MTb) was detected on culture in 5 cases, 3 cases by polymerase chain reaction and caseating granulomas in 25 cases. None of these patients had any symptoms of systemic tuberculosis (TB). Biopsy was inconclusive in eight cases. Granulomatous inflammation was seen in 91 cases. In 51 cases, it was difficult to differentiate between sarcoidosis and TB on biopsy. None of the patients had any significant complications. There was a fair agreement between the biopsy diagnosis and the final ocular diagnosis. Conclusions : In high TB endemic countries, procedures like EBUS-TBNA are useful in obtaining tissue diagnosis of TB when ocular diagnosis may be inconclusive due to paucity of ocular tissue.